ORGINAL ARTICLECreutzfeldt-Jakob disease in Hungary - Kovacs, Gabor G.; Majtenyi, Katalin (Folia Neuropathologica, 2005)
Human prion diseases or transmissible spongiform encephalopathies are progressive fatal neuropsychiatric diseases. In addition to the evaluation of clinical features, a common diagnostic procedure includes examination of the protein 14-3-3 in the cerebrospinal fluid, performing EEG to detect periodic sharp wave complexes with triphasic morphology, and cranial MRI to demonstrate high signal intensity in the basal ganglia or thalamus. The definite diagnosis requires a neuropathological examination. The analysis of the prion protein gene (PRNP) is initiated mainly after suspicion of a positive family history or an atypical presentation. In Hungary collecting data and setting up the neuropathological diagnosis in suspect prion disease cases originates from the late 1960s. Systematic surveillance was established in 1994 and since 2001 reporting of Creutzfeldt-Jakob disease has been compulsory. According to our database, the incidence of genetic prion disease is increased in Hungary. The most frequent mutation in the PRNP is at codon 200. This might be linked to migration from the Slovakian focus. Acquired forms of prion disease were not detected in our country. The surveillance system is based on referrals from clinicians and pathologists and the aim is to perform the neuropathological examination and analysis of the PRNP on the majority of suspect cases.